2020
DOI: 10.3390/jrfm13020034
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Country Application of Manufacturing Failure Models

Abstract: The post-Altman models suffer from moral amortization. This paper asks whether models developed in one country can be applied in other economies. One of the characteristics of the prediction model is that a date drives the estimation. Thus, the estimated model based on one economy is not necessarily applicable to other economies. To verify such a statement, we carried out a literature review to identify the manufacturing models constructed during the last 30 years that were reported in reputable scientific jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The citation count regression method [56,57] consists of reducing a large number of articles to a smaller sample. In this method, the selection of the sample is not random, and the selected articles should be characterized by a great diversity of content.…”
Section: Appendix A2 Outline Of the Methodsmentioning
confidence: 99%
“…The citation count regression method [56,57] consists of reducing a large number of articles to a smaller sample. In this method, the selection of the sample is not random, and the selected articles should be characterized by a great diversity of content.…”
Section: Appendix A2 Outline Of the Methodsmentioning
confidence: 99%
“…Prusak presents "(…) the review and assessment of the level of advancement of bankruptcy prediction research in countries of the former Eastern Bloc, in comparison to the latest global research trends in this area (…)" 12 . Tomczak and Staszkiewicz consider that "(…) the estimated model based on one economy is not necessarily applicable to other economies(…)" 13 . This supports the need for new implementation methods such as, for example, fsQCA, that could be adjusted to evaluate the risk of corporate bankruptcy during the COVID-19 outbreak.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Regression analysis a statistical technique which is used identifying the variables and also the technique is useful to determine the suitable regression strategy for citation data [84]. For regression count, some models can be used in previous research studies were suggested [85][86][87]. A pooled OLS model was employed in our analysis with the year dummy included in the model.…”
Section: Regression Analysismentioning
confidence: 99%